Effectiveness of implementation strategies for venous leg ulcer guidelines: A systematic review. Issue 3 (August 2020) - Kerr, Justin; Devane, Declan; Ivory, John; Weller, Carolina; Gethin, Georgina
Abstract: Background: The aim of clinical practice guidelines (CPGs) is to improve patient care; however inconsistencies between recommended practice and what actually happens in clinical practice continues. Venous Leg Ulcers (VLUs) have a significant negative impact on patients' quality of life and it is acknowledged that managing people with venous leg ulcers is protracted and costly. The aim of this review is to identify the most effective strategies to implement clinical practice guidelines for the management of VLUs by health care professionals in the hospital, outpatient, home and community setting. Methods: A systematic review guided by methods from the Cochrane Effective Practice and Organisation of Care (EPOC) group was undertaken to identify implementation strategies for VLU clinical practice guidelines. Eligible studies were identified via systematic electronic searches of Medline, Embase, CINHAL and the Cochrane Library. Results: We identified 142 potential studies of which one randomised controlled trial met the inclusion criteria. Following an analysis of the included study, it is not possible to recommend one implementation strategy over another when implementing practice guidelines for people with VLUs. Conclusion: We identified a limited evidence base for the effectiveness of implementation strategies for VLU CPGs. No one implementation strategy is better than another to facilitate VLU CPG implementation by health care professionals in hospital, outpatient, home or community settings.